Two Narrative Approaches to Mapuche Culture: Identity Issues, Territorial Reconfigurations, and Discursive Rearticulations in "Piñen and Weichafe" - Ramírez-López, Wilmar A. (2025)
This paper analyzes the ways in which Piñen by Daniela Catrileo and Weichafe by Marcelo Leonart represent, from both internal and external focalizations, various issues related to Mapuche culture. Within these perspectives, identity and territorial questions stand out, situated in contexts marked by multicultural models and other processes of social marginalization, as well as reterritorializations that, through an aesthetic effect of estrangement, promote the emergence of new intercultural dialogic paradigms.